THE ANALYSIS OF STUDENTS’ READING COMPREHENSION ABILITY AT INDONESIAN MARITIME ACADEMY, MEDAN - Digeyasa, I Wy.; Naibaho, Lamhot (International Journal of Research -GRANTHAALAYAH, 2021)
This study is about the analysis of students’ reading comprehension ability, it is done to find out how students’ reading comprehension ability. This study was done at Indonesian Maritime Academy, Medan. The method of the study was quantitative with survey design. The instrument of the study used was a set of reading comprehension test which were constructed based on the taxonomic level. The respondent of this study were 83 respondents who were randomly selected, consisting of two students who studied English for almost two years at Indonesian Maritime Academy, Medan. The result is that the level of students’ reading comprehension among students is at the moderate level and there is a significant relationship between reading comprehension and English language achievement. In conclusion, one way to improve student achievement in English language subjects is by increasing the level of students ’reading comprehension.